Autonomic nervous system mediates the hypotensive effects of aqueous and residual methanolic extracts of Syzygium polyanthum(Wight) Walp.var.polyanthum leaves in anaesthetized rats - Ismail, Azlini; Mohamed, M.; Sulaiman, Siti Amrah; Wan Ahmad, W. A. N. (Hindawi Publishing Corporation, 2013)
Syzygium polyanthum (Wight) Walp. var. polyanthum leaves are consumed as a traditional Malay treatment of hypertension. This study investigates hypotensive potential of aqueous (AESP) and residual methanolic (met-AESP) extracts of S. polyanthum leaves and possible involvement of autonomic receptors. AESP and met-AESP (20 to 100 mg/kg) were intravenously administered into anaesthetized Wistar-Kyoto (WKY) and spontaneously hypertensive (SHR) rats. Blood pressure and heart were monitored for 20 min. AESP and met-AESP induced significant dose-dependent hypotension, but only 100 mg/kg AESP caused mild bradycardia (